The role of sea ice algae-produced carbon in Arctic and Antarctic food webs : dependency of polar life on a threatened food source - Kohlbach, Doreen (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
The underside of sea ice in Polar Regions represents a natural habitat for heterotrophic organisms, such as copepods and amphipods. This under-ice fauna plays a key role in transferring carbon synthesized by sea ice-associated (sympagic) microalgae into associated pelagic and benthic food webs of polar ecosystems. Animals at higher trophic levels are adapted to feed on the under-ice fauna as well as on pelagic zooplankton and nekton. Polar ecosystems thrive significantly on ice algae-produced carbon depending on different periods of the year. Thus, the under-ice fauna and the associated pelagic food web are largely affected by multi-scale climate changes accompanied by the reduction of sea ice coverage and an increasing duration of the melt season. Until now, however, the degree to which polar food webs depend on sea ice-derived carbon is unclear. The overall aim of this thesis is to quantify the transfer of ice algae-produced carbon from the sea ice into the under-ice community and from there into pelagic food webs in Arctic and Antarctic ecosystems, in order to improve our understanding of the potential ecological consequences of a changing sea ice environment for marine food web dynamics. Furthermore, spatial and seasonal differences in the utilization of ice algae-produced carbon within and between both hemispheres are investigated. Die Unterseite des Meereises in den Polargebieten bietet einen natürlichen Lebensraum für heterotrophe Organismen, wie zum Beispiel für Ruderfußkrebse (Copepoda) und Flohkrebse (Amphipoda). Diese Untereisfauna spielt eine wichtige Rolle für die Weitergabe von durch Eisalgen produziertem Kohlenstoff in assoziierte pelagische und benthische Nahrungsnetze in Arktis und Antarktis. Höhere Organismen ernähren sich zum einen von diesen eis-assoziieren Organismen, aber auch von pelagischem Zooplankton und Nekton. Polare Ökosysteme können, je nach Jahreszeit, stark abhängig von dem von Eisalgen produzierten Kohlenstoff sein. Daher sind Untereis-Organismen und assoziierte pelagische ...